Functionally graded electroactive Poly(vinylidene fluoride) polymers. (2nd August 2010) - Costa, C.M.; Gomes, J.; Nunes, J. Serrado; Sencadas, V.; , S. Lanceros-Mendez
The phase transformation from α to β Poly(vinylidene fluoride) (PVDF) through an stretching process at a given temperature and stretching ratio allows controlling the phase content and therefore the electroactive properties of the polymer. Inhomogeneous stretching allows tailoring these properties along a given sample and to obtain graded electroactive and optical properties within the same plate of material from the micro to the macroscopic scale, increasing the potential of PVDF for advance applications.